Morphological growth criterion for faceted to non-faceted transition in pure materials - Bensah, Y.D. (Results in Physics, 2023)
A criterion to explain the morphological growth transition from faceted to non-faceted (f-nf) morphology in the case of directional solidification is presented for pure materials. The criterion is based on the number of atomic layers at the solid–liquid interface and allows a foreknowledge of the solidification growth velocity at which f-nf transition becomes significant. The basis for the transition criterion hinges on the Cahn theory of interface structure and the theory of liquid–solid transition by the maximum entropy production rate (MEPR) principle. The criterion is tested with a number of pure materials and compared with experimental measurements for salol. The criterion fits quite well with available experimental data.
Research Article
Keywords: Maximum entropy generation rate density; Solidification; Morphological transition